2018
DOI: 10.3892/etm.2018.5796
|View full text |Cite
|
Sign up to set email alerts
|

Age‑related changes of the spinal cord: A biomechanical study

Abstract: Although it is known that aging plays an important role in the incidence and progression of cervical spondylotic myelopathy (CSM), the underlying mechanism is unclear. Studies that used fresh bovine cervical spinal cord report the gray matter of the cervical spinal cord as being more rigid and fragile than the white matter. However, there are no reports regarding the association between aging an tensile and Finite Element Method (FEM). Therefore, FEM was used based on the data pertaining to the mechanical feat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 20 publications
1
13
0
1
Order By: Relevance
“…The second factor is the solubility and surface hydrophilicity of SGOB1, which allow even distribution of reduced graphene oxide in the semiconductive SB matrix, thereby assuring an ideal electroconductivity for neuronal differentiation. , Another factor is the role of the mechanical cue in the determination of cell differentiation . A recent investigation of fresh bovine cervical spinal cord mechanical properties put the tensile strength within 60–112 kPa, which is within the range of what we obtained from our novel SGOB1 bioink …”
Section: Resultssupporting
confidence: 67%
See 2 more Smart Citations
“…The second factor is the solubility and surface hydrophilicity of SGOB1, which allow even distribution of reduced graphene oxide in the semiconductive SB matrix, thereby assuring an ideal electroconductivity for neuronal differentiation. , Another factor is the role of the mechanical cue in the determination of cell differentiation . A recent investigation of fresh bovine cervical spinal cord mechanical properties put the tensile strength within 60–112 kPa, which is within the range of what we obtained from our novel SGOB1 bioink …”
Section: Resultssupporting
confidence: 67%
“…44 A recent investigation of fresh bovine cervical spinal cord mechanical properties put the tensile strength within 60−112 kPa, which is within the range of what we obtained from our novel SGOB1 bioink. 49…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 17 , 114 Mechanical stress will also be influenced by the different mechanical properties and tolerance of microstructures within the spinal cord, for example, the white vs gray matter, or relative myelin content of spinal cord pathways 115 which are also subject to change, for example, with age and evolution of injury. 50 , 116 …”
Section: Introductionmentioning
confidence: 99%
“…They demonstrated that changes to both white and gray matter structures increased measured mechanical stress, with changes to the white matter most significant. 153 Okazaki et al 116 (2018) comparing young and old bovine spinal cord specimen demonstrated different tensile and compression stress patterns, in particular, during compression modeling within young specimen, stress was largely confined to white matter structures, whereas in older specimen distributed throughout the spinal cord.…”
Section: Introductionmentioning
confidence: 99%